Phytochrome B Positively Regulates Red Light-Mediated ER Stress Response in Arabidopsis - Ahn, Gyeongik; Jung, In Jung; Cha, Joon-Yung; Jeong, Song Yi; Shin, Gyeong-Im; Ji, Myung Geun; Kim, Min Gab; Lee, Sang Yeol; Kim, Woe-Yeon (Frontiers in Plant Science, 2022)
Light plays a crucial role in plant growth and development, and light signaling is integrated with various stress responses to adapt to different environmental changes. During this process, excessive protein synthesis overwhelms the protein-folding ability of the endoplasmic reticulum (ER), causing ER stress. Although crosstalk between light signaling and ER stress response has been reported in plants, the molecular mechanisms underlying this crosstalk are poorly understood. Here, we demonstrate that the photoreceptor phytochrome B (phyB) induces the expression of ER luminal protein chaperones as well as that of unfolded protein response (UPR) genes. The phyB-5 mutant was less sensitive to tunicamycin (TM)-induced ER stress than were the wild-type plants, whereas phyB-overexpressing plants displayed a more sensitive phenotype under white light conditions. ER stress response genes (BiP2 and BiP3), UPR-related bZIP transcription factors (bZIP17, bZIP28, and bZIP60), and programmed cell death (PCD)-associated genes (OXI1, NRP1, and MC8) were upregulated in phyB-overexpressing plants, but not in phyB-5, under ER stress conditions. The ER stress-sensitive phenotype of phyB-5 under red light conditions was eliminated with a reduction in photo-equilibrium by far-red light and darkness. The N-terminal domain of phyB is essential for signal transduction of the ER stress response in the nucleus, which is similar to light signaling. Taken together, our results suggest that phyB integrates light signaling with the UPR to relieve ER stress and maintain proper plant growth.